Intimate partner violence and associated factors among married adolescent girls and young women in the pastoralist community of South Ethiopia: is intimate partner violence associated with cultural phenomena? - Namer, Ergudo; Shimbre, Mulugeta Shegaze; Alagaw, Amsalu; Guyo, Tamirat Gezahegn (Frontiers in Public Health, 2024)
Background: Violence against women is a main public health problem that affects the physical, sexual, mental, and social well-being of more than one-third of all women worldwide. Hence, the purpose of this study was to determine the prevalence of physical and sexual intimate partner 2 violence and associated factors among married adolescent girls and young women (AGYW) in the pastoralist community of Dassenech district, South Omo Zone, South Ethiopia. Methods: Community-based cross-sectional survey was employed in the Dassenech district among married AGYW from March 01, 2022, to April 01, 2022. A multi-stage sampling technique was employed to select 545 participants. The data were collected using pre-tested and standardized World Health Organization multi-country study tools. A binary logistic regression model was fitted to identify independent predictors of physical and sexual intimate partner violence. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to measure the effect size, and finally, a P-value<0.05 was used to declare the statistical significance.The prevalence of intimate partner physical violence was 44.1% (95% confidence interval (CI): 40%, 48%), and sexual intimate partner violence was 39.3% (95% CI: 35%, 43%).The husband only decides for the household (AOR = 11.36; 95% CI: 6.97, 18.53), the father performs the Dimi culture ceremony (AOR = 3.70; 95% CI: 2.22, 6.14), and frequent quarrels (AOR = 2.06; 95% CI: 1.07, 3.99) are significantly associated with physical intimate partner violence. Both partners drank alcohol (AOR = 3.47; 95% CI: 1.94, 6.20), the husband only decided for the household (AOR = 11.23; 95% CI: 6.91, 18.27), and frequent quarrels (AOR = 2.29; 95% CI: 1.15, 4.56) were factors significantly associated with sexual intimate partner violence.Physical and sexual intimate partner violence are significant public health problems in the study area. Therefore, interventional measures to change the attitude of cultural leaders, provide education on risky sexual behavior, and empower women should be encouraged and strengthened to alleviate this significant public health problem.